2018
DOI: 10.3390/cli6040087
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Trend Analysis of Rainfall and Temperature Extremes in the Vea Catchment, Ghana

Abstract: This study examined the trends in annual rainfall and temperature extremes over the Vea catchment for the period 1985–2016, using quality-controlled stations and a high resolution (5 km) Climate Hazards Group InfraRed Precipitation with Station (CHIRPS) data. The CHIRPS gridded precipitation data’s ability in reproducing the climatology of the catchment was evaluated. The extreme rainfall and temperature indices were computed using a RClimdex package by considering seventeen (17) climate change indices from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…Recent evaluations of monthly gridded CHIRPS-v2 data against gauge station observations in West Africa reported a high correlation that is similar to the results reported in this study [15], [18], [28]. The higher accuracy of CHIRPS-v2 data is because the product was generated from high resolution climatology, multiple satellite products and, the algorithm incorporated a bias correction using the gauge station data [12].…”
Section: Discussion 395supporting
confidence: 84%
See 1 more Smart Citation
“…Recent evaluations of monthly gridded CHIRPS-v2 data against gauge station observations in West Africa reported a high correlation that is similar to the results reported in this study [15], [18], [28]. The higher accuracy of CHIRPS-v2 data is because the product was generated from high resolution climatology, multiple satellite products and, the algorithm incorporated a bias correction using the gauge station data [12].…”
Section: Discussion 395supporting
confidence: 84%
“…However, these new gridded layers need rigorous evaluation against existing ground gauge observations to ascertain their accuracy and inform resource managers on which datasets could be appropriate for specific applications or locations. Several studies have attempted to validate gridded time series data for rainfall in West Africa at the catchment [15] or (sub)-national [16] and regional [17] scales. These evaluations revealed significant disparities in the skill of the satellite rainfall estimates.…”
mentioning
confidence: 99%
“…It is widely used in Ethiopia for drought monitoring [38]. It is well demonstrated that CHIRPS can complement the sparse rain gauge network and provide high spatial and temporal resolution for trend analysis [48,49]. The CHIRPS data were accessed from the ftp server (ftp://ftp.chg.ucsb.edu/pub/org/chg/products/CHIRPS-2.0).…”
Section: Datasetsmentioning
confidence: 99%
“…Extreme climatic variability on rainfall and temperature variability has been quantified using coherent analytical procedures and significant warming over wider portion of the globe (Frich et al 2002;Alexander et al 2006); and the authors discussed that there was no uniform temporal and spatial rainfall pattern. Likewise, Bary et al (2018), Byakatonda et al (2018), Labri et al (2018) and Halimatou et al (2017) stated that extreme temperature indices over Africa revealed increasing warming trends. Recent studies on extreme temperature and rainfall in Ethiopia indicated that there was a significant increase in warming indicator values and decrease in cold spell indicator values (Gebrechorkos et al 2018).…”
Section: Introductionmentioning
confidence: 99%